Socio-economic development of Lower Silesia in the period 2004-2022 (2023) - Korenik, Stanisław; Kozak, Alicja (Społeczno-ekonomiczny rozwój Dolnego Śląska w latach 2004-2022 (2023), 2025)
Background: Since 2004, Lower Silesia has experienced substantial socio-economic transformation, marked by continuous improvements in key macroeconomic indicators over the past two decades. Multiple factors have influenced this positive trajectory, among which European Union funding has played a pivotal role. By the end of 2027 the region is expected to have absorbed over €6.5 billion through major EU programmes, significantly contributing to its development. Despite these advancements, the region faces persistent challenges. Disparities in the pace of development are evident across different areas, with some experiencing slower economic growth. Moreover, the region is increasingly affected by adverse demographic and environmental trends, including population decline, population ageing, and a growing frequency of natural disasters, particularly flooding. These issues pose significant risks to the region’s sustainable development and long-term resilience. Aim: The objective is to identify, describe and assess the most important socio-economic changes occurring in the region and its spatial structures in the analysed period. Methodology: The study uses secondary data analysis, an extensive review and critical analysis of the literature on the subject, expert opinions and simple statistical methods, and in selected fragments the phenomenological method. Results: The basic socio-economic trends occurring in the region in the analysed period were identified and described. Implications and recommendations: Socio-economic development in the region shows large and growing disproportions, therefore, within the framework of intraand inter-regional policies, actions should be taken to eliminate unfavourable trends. Originality/value: Current research providing knowledge on socio-economic development in the region.
Biblioteka Regionalisty = Regional Journal, 2025, Nr 25, s. 97-107
Keywords: region; regional development; Lower Silesia; EU programmes; rozwój regionalny; Dolny Śląsk; programy unijne